2014
DOI: 10.1002/app.41675
|View full text |Cite
|
Sign up to set email alerts
|

Influences of liquid electrolyte and polyimide identity on the structure and conductivity of polyimide–poly(ethylene glycol) materials

Abstract: Current fuel cell technology demands improvements for widespread use, and novel polymer materials may be able to achieve the necessary enhancements. This work inspects the composition, structure, and properties of poly(ethylene glycol) (PEG)-aromatic polyimide systems aimed at polymer electrolyte membrane applications, as PEG is a known ion conductor and aromatic polyimides are quite stable. Liquid electrolytes were incorporated into the polymers through soaking to achieve ionic conductivity. By varying polyim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 106 publications
6
17
0
Order By: Relevance
“…Recent studies showed that segmented block copolymer (SBC) membranes comprised of aromatic polyimide (PI) and poly(ethylene glycol) (PEG) doped with an ionic liquid (IL) present an atractive potential to develop a new family of PEMs . In the PI‐PEG copolymer membranes, phase‐separated PEG domains swollen with IL act as the ion conducting phase and the PI phase serves as supporting matrix to provide for the required thermo‐mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that segmented block copolymer (SBC) membranes comprised of aromatic polyimide (PI) and poly(ethylene glycol) (PEG) doped with an ionic liquid (IL) present an atractive potential to develop a new family of PEMs . In the PI‐PEG copolymer membranes, phase‐separated PEG domains swollen with IL act as the ion conducting phase and the PI phase serves as supporting matrix to provide for the required thermo‐mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we carried out detailed investgations of the nanoscale structural changes upon thermal annealing of PI‐PEG SBC membranes swollen with an ionic liquid and the accomanying increases of the ionic conductivity of the membranes. A specific copolymer system, prepared from 4,4′‐(hexafluoroisopropylidene) diphthalic anhydride (6FDA) ( Figure a), 4,4′‐(1,3‐phenylenedioxy)dianiline (PDODA) (Figure b), and bis(3‐aminopropyl) terminated poly(ethylene glycol) (PEG1500, M n ≈ 1500) (Figure c), was studied because the resultant PI‐PEG copolymer (Figure d) showed the best performance among several monomer combinations in the previous work on the impact of the monomer structures, PEG contents, and PEG molecular weights on PEM performances . Also, ethylammonium nitrate (EAN) (Figure e) was used as a representative protic ionic liquid with labile protons because the EAN‐doped PI‐PEG membranes showed the highest ionic conductivity among several ionic liquids including propylammonium nitrate (PAN), methylammonium nitrate (MAN), and dimethylammonium nitrate (DMAN)…”
Section: Introductionmentioning
confidence: 99%
“…Our research was motivated by the need for a material that can work under harsher environments than Nafion and its derivatives. As mentioned in many previous studies [28][29][30][31], challenges remain to overcome issues like needing to work at low operating temperature, requiring high humidity, or high-water absorption that may cause swelling and mechanical instability. Thus, the objective is to find optimal materials that can effectively respond to all or a portion of these challenges.…”
Section: System Designmentioning
confidence: 99%
“…Many attempts have been made to modify the structure of conventional Nafion membranes to improve their operational properties, e.g., by incorporating hygroscopic inorganic nanoparticles like SiO 2 , TiO 2 , and ZrO 2 [24][25][26]. There have also been extensive studies to synthesize entirely different materials from block or random copolymers, e.g., polystyrene sulfonate-block-polymethyl butylene (PSS-b-PMB) copolymers [11], chitosan/phosphotungstic acid [27], polyimides (PIs), and polyethylene glycol (PEG)-containing PI [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Excellent combined properties have made polyimides (PIs) good candidates for varieties of high‐tech applications, such as electrical and electronic devices, advanced displays, energy and aerospace industries . Especially in the aerospace area, the requirement becomes more and more urgent for large‐scale PI films that rely on the adhesive behaviors between PI films themselves.…”
Section: Introductionmentioning
confidence: 99%